Evaluation of Planting Success and Mangrove Habitat Suitability in Various Planting Years in Pasar Rawa Village, Langkat Regency - Ratna Sari; Sutan Sahala Muda Marpaung; Dini Hardiani Has; Aulia Putra Daulay (Jurnal Biologi Tropis, 2023)
Mangroves are a type of tree whose habitat is in areas influenced by sea tides. This research aims to determine the percentage of mangrove plant life and habitat characteristics at the planting location in Pasar Rawa Village in the 2018, 2019, and 2020 planting years. The research location is in the forest area of Pasar Rawa Village, which is administratively located in Gebang District, Langkat Regency, North Sumatra Province. The time of the research was carried out from March to June 2021. The success of planting R. apiculata mangrove species in each planting year is above 80%. Based on the measurement results at the three planting locations, the average thickness of the mud was above 40 cm. This indicates the planting location is suitable for vegetation growth. Salinity, acidity, and dissolved oxygen in all study locations are also suitable for mangrove growth. This study concludes that the survival percentage of mangrove planting in Pasar Swamp Village at three years of planting is above 80% and has suitable habitat characteristics for mangrove growth. The success of planting mangroves is inseparable from the role of the community, which maintains and carries out the planting and the types suitable for planting in that location. Suggestions for this research are that it is necessary to thin the location of the 2020 planting year because the distance is too tight and add even more specific environmental factors, such as substrate and nutrients, for even better results.